What is the correct adjective ending for the following? Mis manos están sec_ a) as b) os c) es d) o e) a
a) as Mis manos están secas. The article for manos is feminine plural (las). Mano/s is one of those nouns that ends in 'o' but is nevertheless feminine. 'Las manos'
Write out the abbreviated electron configuration for Ti.
Ti is number 22 on the periodic table. I could go through all the electron shells and write the different letters and numbers, but the question asks for the abbreviated form, which is a lot less work to write anyway. The commonly accepted way to write that is to go to the last noble gas, one period (row) up, place the noble gas in brackets [ ] and then complete the electron configuration from there. So Ti is on period 4 and need to write the the noble gas (the far-right group) in period 3 in brackets. It's Ar. So I start with [Ar]. Argon in brackets indicates the electron configuration for Argon (1s2 2s2 2p6 3s2 3p6) without having to write it all out. [Ar] From there, simply add on the following electron configuration after Ar up until Ti, which is 4s2 3d2. [Ar] 4s2 3d2 It may also be written [Ar] 3d2 4s2.
Solve for x in the following equation 2x - 43 = 7(-x + b) when: 3x + 4 = 7(b - 3)
I have 2 equations. I am asked to solve for x in the first one. If I can combine the equations, I can end up with one variable, x, rather than 2, x and b. So, the first thing I want to do is single out b in the second equation, so I can plug in "whatever b is equal to" into the first equation. Yes, that will leave me with a whole lot of information, but only one variable. So first, I'll single out b on one side of the second equation I'm given, step by step. 3x + 4 = 7(b - 3) 3x + 4 = 7b - 21 3x - 17 = 7b (3x - 17)/7 = b or flip sides b = (3x - 17)/7 So I've got what b equals now. I'll plug in what b equals (3x - 17)/7 into the first equation 2x - 43 = 7(-x + b) where b is listed. So, all combined, it will look like this: 2x - 43 = 7(-x + (3x - 17)/7) See how b's information, (3x - 17)/7 was put right where b was in the first equation? Now we simplify until we have one x on one side. 2x - 43 = 7(-x + (3x - 17)/7) 2x - 43 = -7x + 3x - 17 2x = -7x + 3x +26 2x = -4x + 26 6x = 26 x = 26/6 x = 13/3 Woohoo!!